Microstructural constraints on magma emplacement and sulfide transport mechanisms - Vukmanovic, Z.; Fiorentini, M.L.; Reddy, Steven; Godel, B. (GEOLOGICAL SOC AMER, INC, 2019)
The poorly constrained nature of the physical transfer of sulfides along magmatic conduits has implications for the genesis and localization of mineral deposits as well as for understanding the large-scale mobility of volatiles and metals across different geochemical reservoirs. Our natural laboratory to address this topic is a sulfide-bearing ultramafic pipe emplaced in the deep crust of the Ivrea-Verbano Zone, northwest Italy. The pipe is composed of volatile-rich peridotite that contains disseminated, blebby, and semimassive sulfides enriched in nickel, copper, and platinum-group elements (PGEs). The integration of electron backscatter diffraction orientation data and three-dimensional (3-D) X-ray computed tomography analyses from this study indicated that (1) most of olivine crystallized upon emplacement of the magma; (2) the shape and texture of the intragranular sulfide blebs, principally hosted within the central portions of the pipe, reflect early sulfide saturation; and (3) marginal areas record higher strain compared to the cores of the pipes. The differences in the size distribution of the sulfide grains between the central and marginal areas of the pipe are due to magma emplacement dynamics. The larger sulfide aggregates forming the bulk of the Ni-Cu-PGE sulfide mineralization along the margins of the pipe are interpreted to have formed by coalescence of a large number of smaller sulfide droplets. The observed sulfide size distribution between the central and marginal areas of the Valmaggia pipe is principally due to the dynamics of the magma upon emplacement, and it locally records the role of water- and carbon dioxide-bearing volatiles in the physical entrainment of dense sulfide liquids. These processes provide a viable mechanism to transport sulfides enriched in chalcophile and siderophile metals from the upper mantle into the lower continental crust, where they may be available for later remobilization into ore systems that may form subsequently in the middle and upper crust.